Adaptive self-interference suppression for full-duplex relays with multiple receive antennas - Emilio Antonio-Rodríguez; R. López-Valcarce (IEEE 13th Int. Workshop on Signal Processing Advances in Wireless Communications (SPAWC 2012), 2012)
In full-duplex relays, simultaneous reception and transmission in the same frequency results in self-interference which distorts the retransmitted signal and makes the relay prone to oscillation. We present an adaptive feedback canceller for multiple-input single-output (MISO) relays, efficiently combining spatial and temporal processing. The receive array is adaptively steered towards the minimum variance distortionless response (MVDR), whereas the temporal filter update is based on a novel low-complexity spectrum shaping scheme which avoids introducing additional delay in the relay station.
Keywords: adaptive signal processing; dynacs; full duplex